Managing School to Develop Students’ Creative Thinking Skills in the Context of Their Learning Styles - Budi Wibowo, Udik; Marini, Arita; Safitri, Desy; Muji Utami, Nidya Chandra; Wahyudi, Apri (Opción, 2019)
This paper reports the research findings, which look offering a model to im- prove students’ creative thinking skills through students’ learning styles at elementary schools in West Jakarta in Indonesia. This model suggested that students’ creative thinking skills could be encouraged by fluency, flexibility, elaboration, and originality. Students’ learning styles are influenced by stu- dents’ visual, auditory, and kinesthetic learning styles. The study sample in- cluded 276 students at grades 4-6 from 12 elementary schools in West Jakarta in Indonesia. The data consists of two sections, i) students’ creative thinking skills: fluency, flexibility, elaboration, and originality; and ii) students’ learn- ing styles: students’ visual, auditory, and kinesthetic learning styles. Analy- sis data applied the Structural Equation Modeling (SEM). The conclusion reached was that this study was able to illuminate on the existing relationship between students’ learning styles and students’ creative thinking skills. Evi- dence has revealed that there is a kind of relationship between students’ crea- tive thinking and its four dimensions, namely, fluency, flexibility, elaboration, and originality. Result of SEM analysis indicated that students’ visual, au- ditory, and kinesthetic learning styles significantly predicted students’ learn- ing styles. Model of developing students’ creative thinking skills should be broadly researched not only with students’ learning styles, but also with other factors.